Reforms to the Country Administrative Division in Albania After 1990 - Hysi, Arben (Mediterranean Journal of Social Sciences, 2012)
Political changes after 1990 necessitated the reorganization and functioning of local government in Albania. As it is known, twolevels of local government function in our country; the first level includes the communes and municipalities, while the second levelincludes the prefectures and counties. At the time being 12 counties and 12 prefectures, 36 districts, 65 municipalities, 309 communesand 3020 villages function in Albania. The functioning of local government is based on: Constitution of the Republic of Albania, Albanianlegislation since 1990 , especially the law no. 8652 which dates back to July 31, 2000 "On organization and functioning of localgovernment", as well as European charter on local autonomy. Legislation for local autonomy and decentralization of government wasdrafted on the basis of Article 13 of the Constitution of Albania. Article 7 guarantees the principle of unity and balance of the localgovernment. The development of administrative reforms in Albania has been influenced by these factors: - administrative tradition of theAlbanian State 1912 - 2011; - world experience ; - economic and cultural administration level; - interests of political class and Albanianstate; - attitude of the people and the local administration. - physical and geographic conditions of the country. Reorganization andadministrative division are conditioned by of the demomographic movement of rural and urban population. Although Albaniangovernment and parliament have repeatedly focused on the topic of organization and functioning of local government, administrativereform in Albania is far from being considered complete.